Effectiveness of Super-plasticizer on High Volume Slag (GGBS) Concrete - Yap, Phui Sze (Universiti Teknologi Petronas, 2006)
This research was conducted to determine the optimum dosage of super-plasticizer for producing highly workable and high strength concrete using high volume of slag (GGBS). Replacement of high volume slag in cement incorporating super-plasticizer will contribute to increased strength; increased workability; reduced porosity and permeability. Super-plasticized high - volume slag with 40% of Portland cement replacement were produced by using different concentration of chemical admixtures which is Naphthalene Formaldehyle Sulphonate also known as Sikament Nl. A 100% of Ordinary Portland Cement for control mix without super-plasticizer was prepared. Seven mixes were using 60 per cent of high volume of GGBS and 40 per cent of Ordinary Portland Cement (OPC) with different percentage of superplasticizer from 0 per cent to 3 per cent; and constant water/cement (w/c) ratio of 0.40, course aggregate (14mm sieve) and sand. The measurement will be conduct under workability, compressive strength, porosity and gas permeability of the concrete. The duration or ages for measuring was divided in to 3-days, 7 -days, 28- days and 90-days. There were 3 samples have to provide for each mix and each type of sample. However, the conclusion of result is still pending due to the slow development of compressive strength of concrete and further research with higher dosage of super-plasticizer.